Breaking barriers to interoperability: assigning spatially and temporally unique identifiers to spaces and buildings - Pyke, Christopher R.; Madan, Isaac (Annals of the New York Academy of Sciences, 2013)
The real estate industry routinely uses specialized information systems for functions, including design, construction, facilities management, brokerage, tax assessment, and utilities. These systems are mature and effective within vertically integrated market segments. However, new questions are reaching across these traditional information silos. For example, buyers may be interested in evaluating the design, energy efficiency characteristics, and operational performance of a commercial building. This requires the integration of information across multiple databases held by different institutions. Today, this type of data integration is difficult to automate and propone to errors due, in part, to the lack of generally accepted building and spaces identifiers. Moving forward, the real estate industry needs a new mechanism to assign identifiers for whole buildings and interior spaces for the purpose of interoperability, data exchange, and integration. This paper describes a systematic process to identify activities occurring at building or within interior spaces to provide a foundation for exchange and interoperability. We demonstrate the application of the approach with a prototype Web application. This concept and demonstration illustrate the elements of a practical interoperability framework that can increase productivity, create new business opportunities, and reduce errors, waste, and redundancy.